A novel heat treatment protocol for human milk - Manzardo, Olimpia A.; Toll, Luisa J.; Müller, Katharina; Nickel, Erika; Jonas, Daniel; Baumgartner, Jana; Wenzel, Folker; Klotz, Daniel (Frontiers in Pediatrics, 2022)
Human milk is the recommended nutrition for premature infants, but it may require processing to ensure microbial safety. The current standard is Holder pasteurisation (HoP), i.e. heating milk at 62.5°C for 30 minutes, which eliminates bacteria but destroys heat labile bioactive HM components. We aimed to test an alternative thermal method, high-temperature short-time (HTST) pasteurisation using a modified Holder pasteurisation platform as this method has shown to preserve proteins in experimental HM flow pasteurisers. We analysed the ability of this batch process to eliminate bacterial species and to retain alkaline phosphatase, secretory immunoglobulin A and lactoferrin in HM. HTST at 72°C/5s and 81°C/5s were as effective as HoP in bacterial count reduction while the retention of bioactive components was only improved at 62°C/5s as compared to HoP. HTST is a promising alternative to HoP but an optimal temperature-time combination needs to be determined for each technical platform separately.